PERUBAHAN MINAT MASYARAKAT JAWA TERHADAP RUMAH MODEL TRADISIONAL JOGLO LIMASAN MENJADI RUMAH MODERN (STUDI KASUS DESA KEMLOKO, GODONG, GROBOGAN, JAWA TENGAH): (Studi Kasus Desa Kemloko, Godong, Grobogan, Jawa Tengah) - Irnawan, Dody; Rahayu, Silvia Yulita Ratih Setyo (JURNAL TEKNOSAINS KODEPENA, 2020)
Purpose: The purpose of this study is to find out what factors cause people's interest to change to be interested in a minimalist home model. This will be related to several determinants seen from the structural factors in the old buildings compared to the building models that are mostly built by the grobogan community. Design/methodology/approach: Javanese community is identical with Joglo Limasan house building which has its own value for Javanese people from several aspects. The structure of the Joglo Limasan house for the Javanese community consisting of four pillars is the main structure supporting this traditional building. Along with the times, there has been a change of function from the aspect of building construction which was once considered a strong structure. There has been a shift in community interest to rebuild houses with joglo-style roofs. Findings: This can be influenced by cost, material, culture and level of difficulty in building. The author identifies through a case study of limasan Joglo house buildings around the Kemloko village which includes rural areas where almost 90% of the houses have joglo limasan roofs. Because the people in this village are migrants with expertise as builders and overseas workers, many people have had a modern home experience with simple and cheaper roof structures. Originality/value/limitations of the study: The results of this identification are to find out what causes people to prefer modern homes over joglo houses.